Effect of Ownership Structure on Corporate Diversification of Listed Firms in Kenya: The Moderating Role of Capital Structure - Peninah Jepkogei Tanui; Josephat Cheboi Yegon; Ronald Bonuke (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose - This paper aimed to examine the moderating role of capital structure in the relationship between institutional and foreign ownerships on corporate diversification of listed firms at the Nairobi Securities Exchange, Kenya. Design/Methodology - The target population comprised of all the 65 listed firms at Nairobi Securities Exchange in Kenya. However, the inclusion criteria were based on all firms listed at the NSE from 2003 to 2017. Findings - Capital structure significantly moderated the relationship between institutional ownership and corporate diversification. However, there was a statistically insignificant moderating effect of capital structure in the relationship between foreign ownership and corporate diversification. Practical Implications - As to increase diversification, listed firms are suggested to have low levels of capital structure and institutional ownership. Furthermore, low levels of foreign ownership and high capital structure is vital in attaining high diversification levels. Originality - The study contribution is the moderating effect of capital structure in institutional ownership - corporate diversification linkage.